EFEKTIVITAS PERATURAN DAERAH NOMOR 2 TAHUN 2000 TENTANG PEMBERANTASAN PELACURAN DI DESA SANUR KAUH DENPASAR SELATAN - I MADE RAHMAWAN ADITYA WISMARA; ANAK AGUNG PUTU WIWIK SUGIANTARI; LIS JULIANTI (Universitas Mahasaraswati Mataram, 2020)
The purpose of this study is to determine the effectiveness of regional regulation number 2 of year 2000 regarding prostitution in the village of Sanur Kauh and to find out the obstacles faced in terms of eradicating commercial sex workers in the village of Sanur Kauh. In this study data analysis is not offside the scope of the sample. This research is deductive, based on theories or general concepts. Descriptive approach is intended to describe the phenomena that exist, both natural phenomena and man-made phenomena. Social facts will be obtained from a breakdown of the activities, behavior, actions of people as well as the overall possibility of interpersonal interaction, then presented to others more clearly about what is obtained from the field. The Village Government took persuasive action, approached community leaders in the Sanur Kauh Village, so that they can help the village government to disseminate the negative impacts of prostitution. Then the City Government and Village Government work together to eradicate the practice of prostitution.